Case studies on domestic refrigerator energy rationing by implementing a hybrid PV-driven condenser cooling system - Moataz M. Abdel-Raouf; M.A. Eid; M. Elsayed; M. Salah Mansour (Case Studies in Thermal Engineering)
The limitations of exploiting renewable energy within a relatively limited surface area have hindered the use of off-grid residential equipment (i.e., refrigerators). The implementation of feasible PV systems is crucial for the energy management of these appliances. Therefore, the current investigation is motivated by promoting heat emissions from refrigerator condensers throughout the day. Ten condenser cooling case studies that incorporated both partially and fully loaded refrigerator storage capacities were examined experimentally. The results of the modified condenser cooling systems, powered by either an electrical grid or a limited (PV) system, were compared to those of the original refrigerator. The experiments show that the blast cooling and freezing efficiency of chilled and frozen products increased by 32 %, 39.4 %, 39.3 %, and 36 %, respectively, when the refrigerator was partially and fully loaded. Nevertheless, the electrical grid showcased the highest level of savings in cases (3) and (9), with a daily energy saving ratio (DESR) of 9.3 % and 5.4 %, respectively. In the same cases, the integration of a hybrid power source that includes a PV panel resulted in the most significant savings of 17.5 % and 11.4 %, respectively. Finally, the novel refrigerator cost analysis indicates that the extra life cycle payback ratio peaked at 12.48 %.